The Influence of Product Quality, Advertising Strength and Customer Loyalty on Purchasing Decisions of Scarlet Whitening in Batam City - Lista D Nainggolan; Winda Evyanto (Lembaga Riset dan Inovasi Al-Matani, 2023)
This study explores the influence of product quality, advertising strength, and customer loyalty on the purchasing decisions of Scarlet Whitening in Batam city using quantitative research methods. Data was collected through distributed questionnaires, analyzed using multiple linear regression techniques. The Likert scale measured the questionnaire, and operational variables were replaced with variable indicators. Data processing utilized the SPSS application. Accidental sampling was employed based on the Lemeshow formula, resulting in 100 respondents. Findings indicate that product quality significantly affects purchasing decisions. However, advertising strength does not significantly influence purchasing decisions. Customer loyalty has a positive impact. There is a positive and significant influence between product quality, advertising strength, and customer loyalty on purchasing decisions. The coefficient of determination suggests that 75.4% of purchasing decisions are explained by these variables, while 24.6% are influenced by unexplored variables. In conclusion, product quality, advertising strength, and customer loyalty collectively influence purchasing decisions.